Effectiveness Of Mindfulness Based Stress Reduction On Depression In Elderly: A Systematic Review - Lindayani, Linlin; Hendra, Agus; Juniarni, Lia; Nurdina, Gina (Journal Of Nursing Practice, 2020)
Background: The elderly are individuals who have entered the age of 60 years (Hurlock, 2004). One of the most common elderly problems that is more commonly found is depression. Currently increasing research and reviews support the efficiency of psychotherapy treatments for depression. Based on traditional interventions Mindfulness Based Stress Reduction (MBSR) therapy is recommended for geriatric depression. MBSR therapy focuses on is one type of mindfulness-based therapy that focuses on training awareness through meditation techniques. By practicing observing body sensations (body scan meditation), individuals can achieve a mindful condition in their daily lives, including when carrying out routine activities such as walking, eating, standing. MBSR aims to change individual relationships with stressful situations and thoughts. This is achieved by decreasing emotional reactions and increasing.Â Purpose: This study aimed to determine the effectiveness of MBSR therapy on the level of depression in the elderly.Â Methods: Literature searches conducted through Google Scholar and PubMed studies published in English, there were 778 articles obtained but only 5 journals met the search criteria.Results: The results of this review show that MBSR therapy has an influence to reduce the level of depression in the elderly and MBSR therapy has no side effects compared to pharmacological therapy.Conclusion: It is hoped that health workers can implement MBSR therapy to reduce the level of depression in the elderly